Evaluation of Plant Crop of Introduced Banana Clones and the Effects of Packing on Fruit Quality - I. Mahmoud, Haroun (Gezira Journal of Agricultural Science, 2021)
Experiments were conducted at the National Institute for the Promotion of Horticultural Exports (NIPHE), University of Gezira, Wad Medani Sudan, during the period of June 1997 to October 1998, to evaluate yield and quality of banana clones introduced from France as to the local cultivar Dwarf Cavendish. The clones included Williams hybrid (WH) 172, 1280, 1281, 1223 and 1266 and Grand Nain.1824  The experiments were arranged in a completely randomized design with three replications. Experiments also included the use of different packaging treatments and their effects on weight loss of banana fruit stored at either 20 or 32 0 C. The results showed that the clones GN 1824 and WH 172 resulted in the highest yield, bunch weight,  number of hands per bunch, number of fingers per hand and the best finger  dimensions. Weight loss for banana fruit held at 20C˚ was significantly lower than that obtained at 32C˚. At both temperatures, unwrapped fruits resulted in significantly higher weight loss followed by fruit packed in perforated polyethylene bags. The intact bags recorded the lowest fruit weight loss.